Kecerdasan Buatan dalam Pembelajaran Personalisasi: Akselerasi Efektivitas Pembelajaran Bahasa Indonesia di Perguruan Tinggi - Wenny Aulia Sari (Journal of Innovation in Teaching and Instructional Media, 2026)
The purpose of this study is to describe the application of artificial intelligence (AI) in personalized learning, analyze student motivation and engagement, and identify lecturers' and students' perceptions of the effectiveness of Indonesian language learning at State Islamic Religious Universities (PTKI). The study used a qualitative approach with a multi-site case study design at UIN Fatmawati Sukarno Bengkulu and IAIN Curup. The informants of this study consisted of 6 lecturers, 12 students, and 2 study program staff. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results show that the application of AI in personalized learning can increase learning motivation, active engagement, and then students in Indonesian language learning. AI helps lecturers map student learning needs more accurately, provide real-time feedback, and adjust learning materials and strategies based on individual student characteristics. However, the implementation of AI still faces obstacles in the form of limited digital infrastructure and lecturers' technological competencies. This study presents a novelty in the form of an AI-based personalized learning model integrated with local religious and cultural values ​​in PTK. The research's implications suggest that AI can be an innovative strategy for creating adaptive, humanistic, and student-centered Indonesian language learning. This research contribution enriches the study of AI integration in language education within religious higher education settings.